Descriptive Analysis on Parameters Process of Nuclear Reactor Primary Core Coolant System - Azmi, Intan Nabina; Kassim, Murizah; Minhat, Mohd Sabri; Wan Yaacob, Wan Fairos; Ibnu Hajar (International Journal of Integrated Engineering, 2026)
This study investigates the relationship between parameters in the primary coolant system of the Reactor TRIGA PUSPATI (RTP), focusing on water temperature, pressure, and flow. The objective is to enhance understanding of system dynamics for fault prediction and condition monitoring, addressing the challenge of ensuring safety and operational integrity in nuclear facilities. Utilizing real-time monitoring data from RTP, the study employs preprocessing, descriptive analysis, correlation analysis, and linear regression. Results reveal significant relationships between temperature sensors and moderate correlations with pressure and flow sensors, indicating variability in system performance over time. Specifically, temperature sensors TT1 and TT2 exhibit a very high positive correlation of 0.97, while temperature sensors TT1 against TT5 and TT2 against TT5 show strong positive correlations of 0.66 and 0.66, respectively. Moderate positive correlations are observed between temperature sensors TT1, PT4, and FT1, ranging from 0.36 to 0.32. Additionally, descriptive analysis of temperature, pressure, and flow parameters between two months indicates variability in system performance. The study's significance lies in its contribution to safety assessments and maintenance planning in nuclear power plants. It emphasizes the importance of using actual operational data for comprehensive analysis and bridging the gap between theoretical knowledge and practical applications in nuclear engineering.